Towards improved cover glasses for photovoltaic devices. (19th August 2020) - Allsopp, Benjamin L.; Orman, Robin; Johnson, Simon R.; Baistow, Ian; Sanderson, Gavin; Sundberg, Peter; Stålhandske, Christina; Grund, Lina; Andersson, Anne; Booth, Jonathan; Bingham, Paul A.; Karlsson, Stefan
Abstract: For the solar energy industry to increase its competitiveness, there is a global drive to lower the cost of solar‐generated electricity. Photovoltaic (PV) module assembly is material‐demanding, and the cover glass constitutes a significant proportion of the cost. Currently, 3‐mm‐thick glass is the predominant cover material for PV modules, accounting for 10%–25% of the total cost. Here, we review the state‐of‐the‐art of cover glasses for PV modules and present our recent results for improvement of the glass. These improvements were demonstrated in terms of mechanical, chemical and optical properties by optimizing the glass composition, including addition of novel dopants, to produce cover glasses that can provide (i) enhanced UV protection of polymeric PV module components, potentially increasing module service lifetimes; (ii) re‐emission of a proportion of the absorbed UV photon energy as visible photons capable of being absorbed by the solar cells, thereby increasing PV module efficiencies and (iii) successful laboratory‐scale demonstration of proof of concept, with increases of 1%–6% in I sc and 1%–8% in I pm . Improvements in both chemical and crack resistance of the cover glass were also achieved through modest chemical reformulation, highlighting what may be achievable within existing manufacturing technology constraints. Abstract : Modifying the cover glass composition can improve crack resistance from 0.5 to 1.5 N, and the chemical resistance can be increased by a factor of three. Doping of Bi2 O3 and Gd2 O3 can effectively reduce the UV transmission and keep the glass essentially free from absorption in the convertible range whilst also providing down‐conversion of UV photons, thereby increasing both the efficiency and the lifetime of PV modules.